Use of endoloop in video-assisted thoracoscopic enucleation of a very rare esophageal tumor. Issue 11 (20th November 2019) - Alwatari, Yahya; Tse, Wayne; Trebska-McGowan, Kasia; Shah, Rachit D
Abstract: A gastrointestinal stromal tumor is an infrequent tumor of the gastrointestinal tract with very rare involvement of the esophagus. We present a case of a patient with dysphagia and a 4 cm submucosal mass. The patient underwent thoracoscopic enucleation with complete resection of the mass. We present case details and operative video highlighting the important surgical steps of exposure and retraction. We believe that the Endoloop is a very useful tool in providing countertraction needed during minimally invasive resection of such lesions.